2013
DOI: 10.1021/la3047643
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Polymerized High Internal Phase Emulsions Synthesized from Surfactant-Stabilized Emulsion Templates

Abstract: In building construction, structural elements, such as lattice girders, are positioned specifically to support the mainframe of a building. This arrangement provides additional structural hierarchy, facilitating the transfer of load to its foundation while keeping the building weight down. We applied the same concept when synthesizing hierarchical open-celled macroporous polymers from high internal phase emulsion (HIPE) templates stabilized by varying concentrations of a polymeric non-ionic surfactant from 0.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 47 publications
(63 reference statements)
2
60
0
Order By: Relevance
“…This is caused by a higher degree coalescence of the template emulsion before polymerization, creating pores which were much larger than those obtained at the end of agitation this makes the final structure more irregular. A similar result was found by Wong et al [31]. Similarly air bubbles entrained into the emulsion will also be larger for a shorter agitation time of the emulsion template.…”
Section: Permeability Of Macroporous Polymerssupporting
confidence: 87%
See 1 more Smart Citation
“…This is caused by a higher degree coalescence of the template emulsion before polymerization, creating pores which were much larger than those obtained at the end of agitation this makes the final structure more irregular. A similar result was found by Wong et al [31]. Similarly air bubbles entrained into the emulsion will also be larger for a shorter agitation time of the emulsion template.…”
Section: Permeability Of Macroporous Polymerssupporting
confidence: 87%
“…This would lead to much larger pores than the original droplet size in the emulsion immediately after blending making it much less trivial to predict pore size of macroporous polymers produced by emulsion templating. Ostwald ripening (coarsening) [29] can also occur within the system leading to a hierarchal pore system, in which much larger pores are embedded in between much smaller ones [30,31]. The rate of coalescence in emulsions was observed to increase at elevated temperatures [32] needed to typically initiate a free-radical polymerization.…”
mentioning
confidence: 99%
“…5d, it can be concluded that there were some pins in the matrix of polyHIPE-3, and those pins may be formed by the dimerization of UPy groups. Multimodal pore size distribution has an important effect on mechanical strength [34]. PolyHIPE with an optimal packing configuration may have good mechanical properties.…”
Section: Resultsmentioning
confidence: 99%
“…Bismarck's group has done many work in this field [29][30][31][32][33][34]. The polyHIPEs were synthesized from HIPEs containing styrene (St, served as monomer) and divinylbenzene (DVB, employed as crosslinker) as the external phase.…”
Section: Introductionmentioning
confidence: 99%
“…Among the commonly used methods including direct templating, block copolymer selfassembly, and direct synthesis [27,28], freeze-drying is the simplest way to prepare aligned porous inorganic, organic and composite materials [29][30][31]20], but the pore size and pore structure can't be easily tuned via freeze-drying. From an application perspective, the direct templating methodology is a versatile approach to product highly porous polymers with connected pores and tunable pore size [32][33][34], such as high internal phase emulsion (HIPEs) technique. This is a biphasic system with the volume fraction of the discontinuous phase as high as above 74.05%.…”
Section: Introductionmentioning
confidence: 99%